Slow Surface Design and Contemporary Technology Applied in Fashion (ModaPalavra e-periódico, 2018)
This article updates the concepts and fundamentals of Surface Design project methodology from a human and ethical approach, inspired by the principles of Slow Design (Strauss e Fuad-Luke, 2008). The text shares theoretical-practical research findings applied to the Surface Design of fashion products with sustainable intent. The objective of the work is to support academics and professional designers presenting new logics of creation and development of contemporary projects committed to the change towards sustainability. To this end, a conceptual tool and its application in real products are shown, exploring new expressive possibilities of contemporary, manual and semi-industrial techniques, such as digital printing, textile bonding and laser cutting, compatible with manufacturing on a low productive scale, that is, Slow Fashion.
Keywords: slow surface design; slow fashion; low-scale textile technologies; surface design